2019
DOI: 10.3390/ijms21010014
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization and Gene Expression Analyses of GATA Transcription Factors in Moso Bamboo (Phyllostachys edulis)

Abstract: Moso bamboo is well-known for its rapid-growth shoots and widespread rhizomes. However, the regulatory genes of these two processes are largely unexplored. GATA transcription factors regulate many developmental processes, but their roles in moso bamboo height control and rhizome development remains unexplored. Here, thirty-one bamboo GATA factors (PeGATAs) were identified, which are evolutionarily closer to rice than Arabidopsis, and their gene expression patterns were analyzed in bamboo development and phytoh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…According to these studies, the GATA genes from dicotyledons, but not from monocots, could be strictly divided into four subfamilies. In our study, we also find that the subfamilies I, II and III of the GATA genes simultaneously occur in both dicotyledons and monocots, but the subfamily IV genes did not exist in monocots [2,6]. It demonstrated that the subfamily IV of GATA genes appeared after the divergence between dicotyledon and monocot.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…According to these studies, the GATA genes from dicotyledons, but not from monocots, could be strictly divided into four subfamilies. In our study, we also find that the subfamilies I, II and III of the GATA genes simultaneously occur in both dicotyledons and monocots, but the subfamily IV genes did not exist in monocots [2,6]. It demonstrated that the subfamily IV of GATA genes appeared after the divergence between dicotyledon and monocot.…”
Section: Discussionsupporting
confidence: 67%
“…In previous studies, the GATA family genes were systematically investigated in A. thaliana and O. sativa [2,40], Solanum lycopersicum [5], Vitis vinifera [8], Phyllostachys edulis [6] and Gossypium genues [7,9]. According to these studies, the GATA genes from dicotyledons, but not from monocots, could be strictly divided into four subfamilies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, peroxidase mediated anthocyanin degradation via direct oxidation of anthocyanin molecules, or first deglycosylation of sugar moieties by β-glucosidases followed by peroxidase oxidation (Fig. 5 a) has been reported in ornamental kales 21 . Similarly, epicatechin-mediated laccase degradation of anthocyanin via oxidation of epicatechin molecules to quinones followed by polymerization with anthocyanin leading its deglycosylation (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Likewise, few previous studies focused on developmental transition associated flavonoid/anthocyanin accumulation and leaf color change to attainment of maturity 17 20 . Additionally, recent studies in various plant species have revealed the involvement anthocyanin degradation enzymes [beta-glucosidases, polyphenol oxidase (PPO), class III peroxidases (POD) and laccases], and well-coordinated plant hormone signaling pathways in regulation of anthocyanin accumulation 21 , 22 . Interestingly, the role of PPO, POD and beta-glucosidases in oxidation of flavonol glycosides responsible for bitter-taste and astringency in tea was recently reported 23 .…”
Section: Introductionmentioning
confidence: 99%